Implementación de un sistema de seguimiento de trayectorias basado en visión artificial para el mini dron Parrot Mambo. - Suarez Benítez Emerson; Duquino Rico Pedro Alfonso (Universidad Antonio Nariño, 2024)
This thesis focuses on the design and development of a trajectory tracking system using computer vision for the Mini Drone Parrot Mambo, implemented in Simulink. The developed algorithm demonstrated a response time approximately 10 seconds faster in simulations compared to experimental tests on tracks 1 and 2. However, significant limitations were identified, such as difficulties adapting to rapid environmental changes, decreased precision under low lighting conditions, and a battery life limited to 6 minutes, which particularly affected tests on track 3. Despite these limitations, all three tracks were successfully completed. These results confirm the feasibility of using computer vision for trajectory tracking, highlighting the need to improve the algorithm to overcome these limitations and ensure more robust performance in future applications.